January Trip (Karakul Circulations: Colonial Economies and the Un_Making of Disciplinary Knowledges in Germany and Namibia, 2020)
78 JPEG files of joint research trip of project team
Keywords: Agriculture; Karakul sheep; Droughts; Postcolonialism; South Africa; Colonisation; Namibia; Swakara; Karakul Circulations; Colonial Economies; Karakul Farming; Germany; Colonial South-West Africa; German Colonialism; Karakul Sheep Industry